Analisis Komparatif Potensi Financial Distress pada PT Charoen Pokphand Indonesia Tbk dan PT Japfa Comfeed Indonesia Tbk - Komang Tri Wahyuni (Nirta Learning Centre, 2026)
This study aims to analyze the comparison of financial distress levels measured using the Current Ratio (CR) and the Altman Z-Score model in PT Charoen Pokphand Indonesia Tbk and PT Japfa Comfeed Indonesia Tbk during the period 2020–2025. The research method used is a quantitative approach with a comparative design, and the sampling technique applied is purposive sampling. Data analysis was conducted using descriptive statistics and the Independent Sample t-test.The results indicate that there is no statistically significant difference between the two companies in terms of Current Ratio and Altman Z-Score. Descriptively, CPIN has an average Current Ratio of 2.201 and a Z-Score of 3.828, while JPFA has an average Current Ratio of 1.717 and a Z-Score of 3.573. Both companies are classified in the safe zone, indicating a healthy financial condition and a low risk of financial distress.The study recommends that companies maintain a balance between liquidity, profitability, and capital structure to sustain financial stability. Investors are advised to use a combination of financial ratios in decision-making, while future researchers are encouraged to expand the sample size and include additional variables to obtain more comprehensive results.